Mechanisms Of Anti-Prolifertative Effect Of Garcinia Hombroniana Essential Oils Leaves In Mcf-7 And Mcf-7/Tamr-1 Human Breast Cancer Cell Lines - Al Kanan, Alaa Taha Yasir (2019)
Background: Breast cancer is the most common cancer affected women and the incidence rate is increasing yearly throughout the world. Tamoxifen is the first-line chemotherapeutic drug used in treating breast cancer patients. However, gynaecological complications and drug resistance are among the major drawback effects of tamoxifen, particularly at 10-15 years of post-treatment. Thereafter, breast cancer recurrence may occur which also contribute to the major causes of breast cancer-related deaths. Garcinia hombroniana (GH) (seashore mangosteen) is a plant that has been reported to possess good cytotoxic effect against the growth of various human cancer cell lines, including the MCF-7. For this reason, the aim of this study was to further investigate the anti-proliferative and apoptotic effects of the essential oil extracted from the leaves of GH against two different types of breast cancer cell lines, MCF-7 and MCF-7/TAMR-1. Methods: The essential oil was extracted by hydrodistillation process from the leaves of GH. The anti-proliferative effects of the essential oil against MCF-7 and MCF-7/TAMR-1 cancer cell lines were determined using MTT assay and measured by a microplate reader. The mechanism of cell death was determined using Annexin V-FITC/propidium iodide staining assay and quantitatively measured by flow cytometry. The human non-cancerous breast cell line, MCF-10A was also included in both assays as comparative control cells to the MCF-7 and MCF-7/TAMR-1 cells.